JBAH 2020
DOI: 10.7176/jbah/10-15-04
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Genetic Advance of Kabuli Chickpea Varieties for Yield and Yield Related Traits in Ethiopia

Abstract: Fourteen Kabuli chickpea varieties released since 1974 were evaluated in 2017 cropping season at Akaki, Chefe Donsa, Debre Zeit, and Jari stations to determine genetic progress in yield and yield associated traits of Kabuli chickpea varieties. The varieties were laid out in a randomized complete block design with three replications. The average rate of increase in grain yield per year over the past 42 years period was 22.35kgha-1 yr-1 with a relative genetic gain of 1.04% year-1 , which was not significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…). Similarly, GenetMengistu et al (2020) and TibebuBelete et al (2017) reported highly signi cant (p ≤ 0.01) and signi cant (p ≤ 0.05) interaction effects on grain yield and other related traits in the Kabuli and Desi type chickpea varieties, respectively.Yasin Goa and Ashamo (2016) and Yasin Goa (2017) also found a signi cant difference in grain yield and its related components among varieties across different locations in Ethiopia.…”
mentioning
confidence: 88%
See 4 more Smart Citations
“…). Similarly, GenetMengistu et al (2020) and TibebuBelete et al (2017) reported highly signi cant (p ≤ 0.01) and signi cant (p ≤ 0.05) interaction effects on grain yield and other related traits in the Kabuli and Desi type chickpea varieties, respectively.Yasin Goa and Ashamo (2016) and Yasin Goa (2017) also found a signi cant difference in grain yield and its related components among varieties across different locations in Ethiopia.…”
mentioning
confidence: 88%
“…Hundred seed weight was signi cantly and negatively associated with the number of pods plant − 1 (r=-0.32) and non-signi cant and negatively associated with the number of seeds pod − 1 (r=-0.14). This is because more seeds per pod might cause a reduction in the average seed size due to competition among seeds for limited food reserves (Genet Mengistu et al, 2020). Finally, there was a negative and signi cant correlation between days of 90% physiological maturity (r=-0.15) and grain yield (Table 10/Fig.…”
Section: Correlation Between Traitsmentioning
confidence: 99%
See 3 more Smart Citations